Gendered Military Operations? Military Missions in Afghanistan and The Democratic Republic of Congo - Randi Solhjell (The Royal Danish Library, 2013)
It is well acknowledged that womenand men, girls and boys are bothactors in and victims of war andpost-conflict situations. Militaryand peace operations reflect thesegender dynamics and genderequality less in their missions.